Vertex component analysis: a fast algorithm to extract endmembers spectra from hyperspectral data - Nascimento, Jose (2014)
Chapter in Book Proceedings with Peer Review First Iberian Conference, IbPRIA 2003, Puerto de Andratx, Mallorca, Spain, JUne 4-6, 2003. Proceedings